Loss of Consciousness and Prolonged Convulsions Due to Amanita Pantherina Intoxication - Handl, Lukáš; Nováček, Martin; Šín, Robin; Čechurová, Lenka (Neuro-endocrinology letters, 2023)
Loss of consciousness ranks among very common causes for emergency medical service actions and is common occurrence in the emergency department. Its differential diagnosis is very broad and includes many possible causes, not in the least an intoxication. The same applies to convulsive states. Clinical course of mushroom poisoning varies depending on the particular fungal species, with some of the species causing loss of consciousness. One typical representative of such species is panther cap (Amanita pantherina). This case report introduces panther cap poisoning, initially presenting in given patient as coma and protracted generalized convulsions. Complex treatment led to withdrawal of neurologic symptoms, circulatory and metabolic stabilisation and subsequent discharge without signs of permanent organ damage.
Keywords: Amanita; bezvědomí; záchvaty; Unconsciousness; otrava houbami; Mushroom Poisoning; Seizures; Humans; lidé